(untitled) (Gestão & Regionalidade, 2024)
The objective was to reflect on the possibilities and limitations of digital transformation in the management of a rural property in the northern region of Rio Grande do Sul. This is exploratory research developed by the single case study strategy, in the northern region of the state of Rio Grande do Sul. The results indicate that the digital transformation in rural properties stems from the context. Maintaining relationships with other organizations participating in the agribusiness innovation ecosystem facilitates access to digital technologies and the training of rural workers to use them. Limitations stem from the limited skills of rural workers to operate intelligent machines in an integrated manner with property management systems. It was concluded that digital technology had an impact on the structure of traditional agriculture, modifying methods, rural production processes, and managerial decisions, as well as improving performance in the production process. At the same time, the training of rural workers and the communications infrastructure available in Brazil limit the use of the potential of intelligent machines.